Imprint of DES superstructures on the cosmic microwave background. Issue 4 (17th November 2016) - Kovács, A.; Sánchez, C.; García-Bellido, J.; Nadathur, S.; Crittenden, R.; Gruen, D.; Huterer, D.; Bacon, D.; Clampitt, J.; DeRose, J.; Dodelson, S.; Gaztañaga, E.; et al.
Abstract: Small temperature anisotropies in the cosmic microwave background (CMB) can be sourced by density perturbations via the late-time integrated Sachs–Wolfe (ISW) effect. Large voids and superclusters are excellent environments to make a localized measurement of this tiny imprint. In some cases excess signals have been reported. We probed these claims with an independent data set, using the first year data of the Dark Energy Survey (DES) in a different footprint, and using a different superstructure finding strategy. We identified 52 large voids and 102 superclusters at redshifts 0.2 < z < 0.65. We used the Jubilee simulation to a priori evaluate the optimal ISW measurement configuration for our compensated top-hat filtering technique, and then performed a stacking measurement of the CMB temperature field based on the DES data. For optimal configurations, we detected a cumulative cold imprint of voids with Δ T f ≈ −5.0 ± 3.7 μK and a hot imprint of superclusters Δ T f ≈ 5.1 ± 3.2 μK; this is ∼1.2σ higher than the expected |Δ T f | ≈ 0.6 μK imprint of such superstructures in Λ cold dark matter (ΛCDM). If we instead use an a posteriori selected filter size ( R / R v = 0.6), we can find a temperature decrement as large as Δ T f ≈ −9.8 ± 4.7 μK for voids, which is ∼2σ above ΛCDM expectations and is comparable to previous measurements made using Sloan Digital Sky Survey superstructure data.